The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33687/phytopath.010.03.3442
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Tomato Mosaic Virus Reduces Lycopene Accumulation in Tomato Fruits

Abstract: Despite Lycopene content in tomato germplasm (both local and exotic) was evaluated against isolates of tomato mosaic virus (ToMV), using a locally preferred hybrid i.e., Rio Grande as a control. Promising lines with resistance to ToMV were assessed by total carotenoid and lycopene content in virus-challenged tomato genotypes using spectrophotometry and RP-HPLC. Our data showed that virus infection significantly lessens the total carotenoid and lycopene content in tomato fruit. Lycopene content was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The results of the study agreed with the results of [19] which showed a decrease in the amount of lycopene in tomato fruits infected with TYLCV compared to non-infected plants. [20] also showed that infection of tested genotypes against Tomato mosaic virus (ToMV) affected the plant content of lycopene present in infected tomato fruits with a significant difference from uninfected plants.…”
Section: Effect Of Infection With Tylcv On the Content Of Lycopene Ge...mentioning
confidence: 97%
See 2 more Smart Citations
“…The results of the study agreed with the results of [19] which showed a decrease in the amount of lycopene in tomato fruits infected with TYLCV compared to non-infected plants. [20] also showed that infection of tested genotypes against Tomato mosaic virus (ToMV) affected the plant content of lycopene present in infected tomato fruits with a significant difference from uninfected plants.…”
Section: Effect Of Infection With Tylcv On the Content Of Lycopene Ge...mentioning
confidence: 97%
“…Consequently, this led to the plant not forming tomato fruits, and if they did, they would be small in size. In addition, the effect of the virus on plant dry weight [15][16][17][18][19][20][21][22][23]. [20] reported that TYLCV infects the phloem cells, causing a decrease in the rates of transport and distribution of nutrients, which leads to a decrease in the level of many materials necessary for building and sustaining plant life.…”
Section: The Effect Of Infection With Tylcv On the Genotypes Of Tomat...mentioning
confidence: 99%
See 1 more Smart Citation